The Correlation Between Spiritual Intelligence With Nursing Performance in Haji Province Hospital of South Sulawesi - Husaeni, Hermin (Universitas Sulawesi Barat, 2019)
Nurses are providers of constant and continuous service for 24 hours to patients. A good nurse's performance is the main key in improving the quality of health services. By increasing and strengthening spiritual intelligence, nurses can protect themselves from the inevitable negative effects of job stress so that they are more effective in improving their performance. The purpose of this study is to analyze the relationship of spiritual intelligence with the performance of nurses at the in Haji Province Hospital of South Sulawesi. The research design uses a quantitative cross-sectional study. The research sample of 70 respondents who were determined by total sampling technique. Data were analyzed by univariate analysis, bivariate chi-square test. Chi-Square test results indicate that spiritual intelligence with nurse performance is worth p = 0.007 which means that there is a relationship between spiritual intelligence and nurse performance. The breakdown of the relationship between performance components and spiritual intelligence is nurse quality p = 0.005, quantity p = 0.005, effectiveness p = 0.021, cooperation p = 0.000, independence p = 0.022, commitment p = 0.001. Based on these data, it can be concluded that there is a relationship between quality, quantity, effectiveness, cooperation, independence and commitment of nurses to nurse performance